2020
DOI: 10.1038/s41598-020-78382-3
|View full text |Cite
|
Sign up to set email alerts
|

Augmented transcripts of kidney injury markers and renin angiotensin system in urine samples of overweight young adults

Abstract: Obesity has been firmly established as a major risk factor for common disease states including hypertension, type 2 diabetes mellitus, and chronic kidney disease. Increased body mass index (BMI) contributes to the activation of both the systemic and intra-tubular renin angiotensin systems (RAS), which are in turn associated with increased blood pressure (BP) and kidney damage. In this cross-sectional study, 43 subjects of normal or increased body weight were examined in order to determine the correlation of BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…This study aimed to evaluate the plasma and urinary NGAL and KIM-1 levels in diabetic children and determine their roles in predicting renal injury. Despite a lack of evidence and age-dependent changes in the reference interval for plasma and urinary NGAL and KIM-1, many publications have highlighted them as promising biomarkers reflecting early renal tubular injury in patients with CKD including DN [18,26,27]. The results of the present study were consistent with those of such previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…This study aimed to evaluate the plasma and urinary NGAL and KIM-1 levels in diabetic children and determine their roles in predicting renal injury. Despite a lack of evidence and age-dependent changes in the reference interval for plasma and urinary NGAL and KIM-1, many publications have highlighted them as promising biomarkers reflecting early renal tubular injury in patients with CKD including DN [18,26,27]. The results of the present study were consistent with those of such previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…Also, CTGF excretion was related to the severity of diabetic nephropathy, suggesting that urinary CTGF may provide a marker of renal injury [ 40 ]. In a cross-sectional study, we reported that the mRNA levels of urinary kidney injury markers such as interleukin-18 (IL-18) and CTGF were augmented in individuals with a high BMI [ 12 ]. However, we did not find any changes in the neutrophil gelatinase-associated lipocalin (NGAL) and kidney injury molecule-1 (KIM-1) mRNA levels [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study, we reported that the mRNA levels of urinary kidney injury markers such as interleukin-18 (IL-18) and CTGF were augmented in individuals with a high BMI [ 12 ]. However, we did not find any changes in the neutrophil gelatinase-associated lipocalin (NGAL) and kidney injury molecule-1 (KIM-1) mRNA levels [ 12 ]. Terami et al showed that uAGT positively correlated with the albumin/creatinine ratio and urinary α1-microglobuline and pointed out that uAGT–α1-microglobulin correlation more accurately reflected the tubular injury associated with the intrarenal RAS activation in patients with T2DM [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation